2022
DOI: 10.3390/curroncol29100578
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Breath Analysis in the Management of Lung Cancer: Is It Ready for Primetime?

Abstract: Breath analysis is a promising non-invasive method for the detection and management of lung cancer. Exhaled breath contains a complex mixture of volatile and non-volatile organic compounds that are produced as end-products of metabolism. Several studies have explored the patterns of these compounds and have postulated that a unique breath signature is emitted in the setting of lung cancer. Most studies have evaluated the use of gas chromatography and mass spectrometry to identify these unique breath signatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 137 publications
0
6
0
Order By: Relevance
“…For example, eNoses have been used to exclude active tuberculosis in an indigenous population, 82 to detect tuberculosis in badgers, 83 and to assist with lung cancer screening. 84 Many of these techniques are currently being evaluated in clinical trials and in population studies.…”
Section: Other Exhaled Breath Biomarkers Volatile Organic Compound As...mentioning
confidence: 99%
“…For example, eNoses have been used to exclude active tuberculosis in an indigenous population, 82 to detect tuberculosis in badgers, 83 and to assist with lung cancer screening. 84 Many of these techniques are currently being evaluated in clinical trials and in population studies.…”
Section: Other Exhaled Breath Biomarkers Volatile Organic Compound As...mentioning
confidence: 99%
“…One such technology which is currently being validated in clinical studies is the analysis of exhaled breath samples using electronic nose (e‐nose) technology 32–34 . E‐nose technology uses machine learning algorithms to assay volatile organic compounds in the exhaled breath of patients, and in translational and preclinical studies it has demonstrated diagnostic accuracy in lung cancer patients as high as 86% 33 .…”
Section: Advancements In Screening and Diagnosismentioning
confidence: 99%
“…One such technology which is currently being validated in clinical studies is the analysis of exhaled breath samples using electronic nose (e-nose) technology. [32][33][34] E-nose technology uses machine learning algorithms to assay volatile organic compounds in the exhaled breath of patients, and in translational and preclinical studies it has demonstrated diagnostic accuracy in lung cancer patients as high as 86%. 33 As its development continues, e-nose technology appears poised to streamline the diagnosis of screen-detected lung cancers by offering reliable, realtime readouts of test results and averting the potential complications of invasive diagnostic procedures.…”
Section: The Role Of Ai In Lung Cancer Diagnosismentioning
confidence: 99%
“…Although there are known biomarkers for the detection of specific cancers (e.g., AFP+CEA+CA125 for primary breast cancer or PSA for prostate cancer), there are currently no blood-based biomarker assays that can predict the development of secondary lung cancer [23] . Even though direct airway collection strategies [i.e., nasal epithelial brushing, sputum, bronchial brushing, bronchioalveolar lavage (BAL), and exhaled breath condensate (EBC)] are being investigated for the detection of primary lung cancer, they have not been evaluated for the detection of secondary lung cancer [24][25][26][27][28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%